Sustainability assessment in bananeira production agroecosystems with the application of the MESMIS method (Research, Society and Development, 2020)
This article is the result of a master's dissertation in environmental sciences, and focuses on the study of the sustainability of banana production agro-ecosystems in the Vale do Açu region, from the point of view of the Management Systems Assessment Framework Incorporating Sustainability Indicators (MESMIS). The objective of the work was to evaluate the sustainability of two agroecosystems, carrying out, for this, a comparative study between the alternative and conventional banana systems. The data were obtained from the performance of exploratory research, semi-structured interviews, laboratory analyzes, observations, and the methodology proposed by MESMIS, so that the systematizations and considerations made by the interviewees were considered to determine the steps of MESMIS. From this, it is concluded that the production of the alternative agroecosystem is more sustainable than that of the conventional, since the first presented a desired situation of sustainability, while the second gave priority to productivity, thus neglecting itself, to the detriment dimensions of socio-environmental sustainability.